Orientalism and Discourse Manifestations According to Edward Saeed - Abduljabbar, Marwa; Alsheikh , Hussein (Al-Adab Journal, 2024)
In this study, we discussed the topic of Orientalism according to Saeed, this Palestinian thinker, who his work in literature did not avoid him from taking the advantage from Michel Foco’s philosophical point of view in founding a critical vision of the Orientalism concept. Saeed accomplished a major cognitive project in criticizing Western culture, as his book “Orientalism” is considered a basic reference that he embodied his critical vision of the hegemonic character of Western culture. Through his analysis of Orientalist discourses, he shed the light on how knowledge was involved in the imperialist project, which served as the methodological framework that justified colonialism, thus revealing the Orientalists’ hidden grudges and the making of preconceived judgments about the East that ultimately express the will to dominate and pave the way for Western colonialism. Edward Saeed was guided by a different approach in analysis, represented by reading Orientalism as a discourse, relying on the tools of discourse analysis according to Michel Foco.